The role of size constancy for the integration of local elements into a global shape - Rennig, Johannes; Karnath, Hans-Otto; Huberle, Elisabeth (Frontiers in Human Neuroscience, 2013)
Visual perception depends on the visual context and is likely to be influenced by size constancy, which predicts a size and distance invariant perception of objects. However, size constancy can also result in optical illusions that allow the manipulation of the perceived size. We thus asked whether the integration of local elements into a global object can be influenced by manipulations of the visual context and size constancy? A set of stimuli was applied in healthy individuals that took advantage of the ‘Kanizsa’ illusion, in which three circles with open wedges oriented towards a center point are placed to form an illusionary perception of a triangle. In addition, a 3D-perspective view was implemented in which the global target (‘Kanizsa’ triangle) was placed in combination with several distractor circles either in a close or a distant position. Subjects were engaged in a global recognition task on the location of the ‘Kanizsa’ triangle. Global recognition of ‘Kanizsa’ triangles improved with a decreasing length of the illusory contour. Interestingly, recognition of ‘Kanizsa’ triangles decreased when they were perceived as if they were located further away. We conclude that the integration of local elements into a global object is dependent on the visual context and dominated by size constancy.